Integrasi Robot Lengan Beroda Holonomic dan Pengindraan Visual Menggunakan Yolov5 untuk Pemilah Sampah - Chaidir, Ali Rizal; Herdiyanto, Dedy Wahyu; Anam, Khairul (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2025)
The issue of waste management has become a critical topic, particularly in the sorting process, which relies on human labor and poses hygiene risks and inaccuracy. Several technologies have been explored to address this problem, including robotic arms with visual sensing, which are widely used but face challenges such as limited working areas and relatively complex installation processes. This study develops a waste-sorting robot based on a holonomic-wheeled robot integrated with visual sensing and the YOLOv5 algorithm for waste classification. The robot is equipped with a vacuum gripper for waste pickup and placement, as well as sensors for navigation and position control. Tests were conducted on four types of waste: bottles, leaves, metals, and paper. The results demonstrate a classification accuracy rate of 100%, with an average waste placement success rate of 90% for leaves and paper, and 80% for bottles, influenced by the surface characteristics of the waste and the consistency of the robot's positioning. This robotic system offers enhanced efficiency and accuracy compared to manual methods, although there remains room for improvement in the gripping mechanism and synchronization of the robot's movements. Overall, the robot system shows performance with accuracy above 80% with a wider working area than using a robot arm.